2022
DOI: 10.1038/s41598-022-26019-y
|View full text |Cite
|
Sign up to set email alerts
|

A lower sleep regularity index (SRI) is associated with relapse in individuals with alcohol use disorder following inpatient treatment

Abstract: The sleep regularity index (SRI) is used to measure an individual’s sleep/wake consistency over time. The SRI has been associated with certain health risks; to date, research investigating the relationship between the SRI and relapse in individuals with alcohol use disorder (AUD) is lacking. The aim of this work was to evaluate the SRI and relapse in individuals with AUD following inpatient treatment. Individuals with AUD (n = 77, mean age = 49.5 ± 10.86) were assessed for 28-days following discharge from an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Other potential explanations for the different gut microbiome and metabolome found among AB individuals may be attributed to the mental health differences observed. Previous studies have shown perturbations of the gut microbiome in multiple psychiatric disorders [ 4 , 85 , 86 ] as well as sleep disturbances [ 87 ]. A recent review and meta-analysis of 34 studies on the gut microbiome of individuals affected by various psychiatric disorders revealed a significant decrease in microbial community richness compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential explanations for the different gut microbiome and metabolome found among AB individuals may be attributed to the mental health differences observed. Previous studies have shown perturbations of the gut microbiome in multiple psychiatric disorders [ 4 , 85 , 86 ] as well as sleep disturbances [ 87 ]. A recent review and meta-analysis of 34 studies on the gut microbiome of individuals affected by various psychiatric disorders revealed a significant decrease in microbial community richness compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%